Can monocyte/HDL ratio predict the mortality in acute pulmonary embolism? - Telo, Selda; Kuluöztürk, Mutlu; Kırkıl, Gamze (Yuzuncu Yil Universitesi Tip Fakultesi, 2024)
In recent times, monocyte/high-density lipoprotein cholesterol (HDL) ratios (MHR) surfaced as novel markers of inflammation and oxidative stress. This study aims to investigate the short-term prognostic role of the MHR ratios in patients who suffer from acute pulmonary embolism (PE). Two hundred patients who suffered from pulmonary embolism were included ret rospectively in the current study. The demographic data along with the laboratory parameters of the patients were obtained from the digital archive system of the facility. Mortality was seen in 42 (21%) of 200 patients with PE. It was determined that the mean age, mean troponin level, pulmonary artery pressure, monocyte value, and MHR ratios were statistically higher in exitus group compared to the survivor group. The mean MHR value was higher in patients with exitus in 1st month than patients with exitus between 1-6 months (p=0.009). 132 (66%) patients with acute PE had sPESI ?1, while mean MHR was statistically higher in high-risk patients compared to low-risk PE patients (17.95±12.67, 11.54±5.66, p= 0.001, respectively). For the MHR ratio, when the cut-off value was considered 16.03 in the prediction of PE cases for survival, the sensitivity was 81% and the specificity was 62% (AUC=0.793, p=0.001, CI%= 0.722-0.865) The fact that MHR was higher in exitus group, in high-risk patients and in those patients with exitus in the first 1 month suggested that it may be an important factor in predicting mortality in patients with PE. © 2024, Yuzuncu Yil Universitesi Tip Fakultesi. All rights reserved.
Keywords: Monocyte/HDL ratio; Mortality; PESI; Pulmonary embolism